Testing for taxonomic bias in the future diversity of Australian Odonata. Issue 9 (19th March 2014) - Bush, Alex; Nipperess, David A.; Theischinger, Gunther; Turak, Eren; Hughes, Lesley; Burridge, Chris
Abstract Aim Invertebrates are often overlooked in assessments of climate change impacts. Odonata (dragonflies and damselflies) are a significant component of freshwater macroinvertebrate diversity and are likely to be highly responsive to a changing climate. We investigate whether climate change could lead to significant alteration of continental patterns of diversity and whether vulnerable species are taxonomically clustered. Location Australia. Methods Habitat suitability of 270 odonate species was modelled, and a simplified phylogeny was developed based on taxonomic relationships and expert opinion. These maps were then combined to compare species richness, endemism, taxonomic diversity (TD) and taxonomic endemism (TE) under climate change scenarios, and estimate turnover in species composition. Based on the concentration of vulnerable species in regions associated with Gondwanan relicts, we tested the possibility that a focus on species loss would underestimate loss of evolutionary diversity. Results Species richness of Australian Odonata is concentrated in the Wet Tropics, central‐north Australia and south‐east Queensland. Several additional regions support endemic assemblages, including the Victorian alpine region, the Pilbara and far south‐western Australia. Major shifts in composition are expected across most of the east coast in response to climate change, and Tasmania has the potential to become a major refuge for mainland species. For many regions, the loss of TD is greater than expected based on the changes in species richness, and the loss of suitable habitat was unevenly distributed among families. However, the potential loss of evolutionary diversity among vulnerable species was not significantly different from random. Main conclusions The major shifts in the distribution of Australian odonate diversity predicted to occur under climate change imply major challenges for conservation of freshwater biodiversity overall. Although major evolutionary losses may be avoided, climate change is still a serious threat to Australia's Odonata and poses an even greater threat to Australian freshwater biodiversity as a whole.